The Correlation Between Generic Science Skill and Biology Learning Results of Public Junior High schools in Ambon Using Scientific Approach - Prelly M.J Tuapattinaya; Dominggus Rumahlatu (Intelektual Pustaka Media Utama, 2018)
The purpose of this research was to determine the correlation between generic science skills and students’ Biology learning results on plant movement material in Junior High Schools in Ambon using scientific approach. This is a correlational research using the instruments of the rubric of generic science skill and cognitive tests. The design of this reserch is the analysis of the effect of generic science skill variables (X1) and the school origin (X2) toward the students’ learning results (Y) with the design of one group pretest-posttest. The data ontained were descriptively analyzed and through covariate analysis and correlation analysis. The results of this research showed that learning by using scientific approach had the average score of 0.740 with high category (Junior High School 6 Ambon), while learning using conventional approach had an average score of 0.219 with low category (Junior high school 9 Ambon). The biology learning result score of the students in some junior high schools in Ambon on the material of plant movement systems taught by using scientific approach experienced an increase, inwhich the students’ biology learning results after taught by using scientific approach achieved 85.68-100.00% with very good category compared to that taught by using the conventional approach, which was 39.51-89.04% with fair until very good catagory. In addition there was a strong correlation (r=0.6) between generic science skills and biology learning results on the conceptof plant movement of Junior High School students in Ambon.